Faktor Penyebab Kematian Ibu Hamil Dengan Preeklampsia Di Wilayah Kerja Puskesmas Klareyan Kabupaten Pemalang - Yohanes Teguh Pambudi; Rifatolistia Tampubolon; Gelora Mangalik (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: This study is to analyze the factors that cause the high mortality rate of pregnant women with preeclamsia in the Klareyan Health Center, Pemalang RegencyMethods: This research is descriptive qualitative with a retrospective case study approach. The data were collected through interview guides that had been conducted through in-depth interviews. The data from the interviews are processed into data coding and then analyzed interactively.Results: The results of data analysis from coding obtained several themes related to the factors causing death of pregnant women with preeclampsia in the form of the following themes: maternal consumption patterns and daily life patterns during pregnancy, knowledge of mothers and families about preeclampsia during pregnancy, lack of role and support of families for pregnant women with preeclampsia, the role of puskesmas in providing health services is hampered by the behavior of pregnant women with preeclampsiaConclusion: The factors causing the high mortality rate of pregnant women with preeclampsia at the Klareyan Public Health Center, Pemalang Regency are the mother's consumption pattern and daily lifestyle during pregnancy, knowledge of mothers and families about preeclampsia during pregnancy, lack of role and family support for pregnant women with preeclampsia, the role of puskesmas in providing health services is hampered by the behavior of pregnant women with preeclampsia.